SYNYHESIS AND ANTIFUNGAL ACTIVITY OF SOME NEWLY SYNTHESIZED SUBSTITUTED 1,2,4-TRIAZOLO- 1,3,4 THIADIAZOLES - Anil Kumar (International Journal of Research Science and Management, 2014)
A novel series of substituted 1,2,4 Triazolo-1,3,4 Thiadiazoles were synthesized by the cyclo dehydration of substituted 1,3,4 thiadiazole-2 thioles with suitable semicarbazide and potassium salt of substituted 1- Hydrazine carbodithionic acid in presence of Conc. H2SO4 .The newly synthesized compound were characterized by IR and 1HNMR spectra and were screened for their promising antifungal activity against A. Solani and A. Tenius. Some of newly synthesized compounds show their promising antifungal activity